Corrigendum on 'OH Density Measurements by Time‐Resolved Broad Band Absorption Spectroscopy in a He‐H2O Dielectric Barrier Discharge With Small O2 Addition'. Issue 2 (15th May 2015) - Martini, Luca Matteo; Dilecce, Giorgio; Scotoni, Mario; Tosi, Paolo; De Benedictis, Santolo
Abstract : In this note, it is described a factor of two correction to our previously published OH density measurements by broad‐band absorption in a He‐H2 O‐O2 dielectric barrier discharge (PP&P 2014 vol.11 p.232–238 ).